WOMEN'S EMPOWERMENT THROUGH WASTE RECYCLING AS AN IMPLEMENTATION OF GREEN ECONOMY AT CV. WITAMA PLASTINDO - Winih, Titik Sri; Wahyudi, Amin; Marpuah, Siti (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The purpose of this study is to analyze the implementation of women's empowerment through waste recycling as a form of the implementation of going green economy in Ponorogo. The waste problem has become a universal phenomenon in various parts of the world. Empowering women through waste recycling is an effort to improve the community's economy, especially women. The research method here is field research with a qualitative approach. In obtaining information, researchers use primary data sources as well as secondary data sources. Primary data is obtained from interviews, Observation, and documentation, while secondary data is obtained from books, articles, and journals that support it. Interviews in this study were conducted with woven bag business owners, as well as women who participated in empowerment programs. The results showed that the process of empowering women through waste recycling went quite well. The women were given training and also assistance on how to make woven bags. In the implementation of this empowerment carried out by CV Witama Plastindo which was then facilitated by the industry and social services. The targets here are women who work as farmers. The impact of the implementation of this empowerment is that they in terms of income have increased even though they are still far from the UMR.